Summary Report, Canadian Geoscience Council Review Committee on the Minerals Geoscience Program of the Geological Survey of Canada - Cathro, R.; Jacques, A.; Lesher, C.; Swinden, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary An external review committee, appointed by the Canadian Geoscience Council in 1999, has investigated the scope, relevance, project selection, strategic planning, management, and program evaluation of the Minerals Geoscience Program (MGP) of the Geological Survey ofCanada. The MGP has been negatively impacted by government policies and organizational changes, including a decline in funding of almost 50% in the previous 6 years as a consequence of government-wide cutbacks. The review committee has made a number of recommendations to strengthen minerals research at the GSC. The most important of these are setting clear strategic directions, aligning and prioritizing projects with strategic goals, and taking advantage of new opportunities for greater collaboration and synergy, both within the GSC and with provincial surveys, universities and industry.